Policies for a more efficient and inclusive housing market in Luxembourg - Stráský, Jan (OECD Economics Department Working Papers, 2020)
Housing prices have been growing strongly in Luxembourg, stoked by population growth, a high rate of household formation and limited use of land available for construction. Increases in price-to-income ratio mainly reflect high valuations of residential real estate, which rise faster than incomes, leading to increasing financial risks related to household indebtedness. Housing affordability has been deteriorating in particular for low-income households who do not profit from highly subsidised social housing. A mix of policies addressing supply-side restrictions, such as land hoarding and resistance to densification, together with policies to increase housing tenure neutrality and better targeted fiscal support will be needed to make the housing market more efficient and inclusive. Measures increasing the opportunity costs of unused land in urbanised areas and unoccupied dwellings could be combined with further reform of land-use planning, including measures involving municipalities in selectively increasing residential density in areas well-connected to the transport network. Housing tenure neutrality could be supported by removing or at least reducing mortgage interest deductibility and other fiscal instruments supporting homeownership and by developing the recurrent taxation of immovable property into a more important fiscal resource based on up-to-date real estate valuations. The supply of social rental housing should be stepped up and access to it made conditional on recurrent means testing ensuring better targeting to those most in need. Private rental sector could be expanded by relaxing the rules on renting parts of housing units and conversion of existing dwellings into rental housing